Efeito de antioxidantes, cloreto de cálcio e luz ultravioleta (UV) pulsante na conservação de manga “Tommy Atkins” minimamente processada - Santos, Josenice Silva dos (2011)
The present study aimed to evaluate the effects of antioxidants (ascorbic acid (AA), citric acid (AC), Ethylene diamine tetra acetic acid (EDTA)) and calcium chloride on the physico-chemical and biochemical caracteristics and pulsed ultraviolet (UV) light on the physico-chemical and antioxidant activity of minimally processed 'Tommy Atkins' mango. The pH, soluble solids content, carotenoid content, browning index, total phenol, vitamin C, total acidity, polyphenyloxidase (PPO) activity, pectinmethylesterase (PME) activity and antioxidant activity were analyzed at an interval of three days. It was found that higher levels of total phenol were found in samples treated with ascorbic acid at 2% and the lowest for the EDTA treatment. The polyphenoloxidase activity was lower for treatment with EDTA 1% during the storage period. Calcium affected the characteristics analyzed, providing a high total pectin content and lower pectinmethylesterase activity. The treatment with calcium chloride at 1.5% was effective in maintaining the integrity of the membrane cell by decreasing the enzymatic pectinmethylesteras activity. The treatment with pulsed UV light influence the ascorbic acid, carotenoids and antioxidant activity after exposure to 12 pulses of samples reaching values of 63.43 mg/100g, 2.19 mg/100 and 7.49 mM trolox / g pulp, respectively. We conclude that 12 pulses was the best for minimally processed 'Tommy Atkins' mango.